Advanced Computational Methods of Rapid and Rigorous 3-D Inversion of Airborne Electromagnetic Data (Communications in Computational Physics, 2008)
We develop a new computational method for modeling and inverting frequency domain airborne electromagnetic (EM) data. Our method is based on the contraction integral equation method for forward EM modeling and on inversion usingthe localized quasi-linear (LQL) approximation followed by the rigorous inversion, ifnecessary. The LQL inversion serves to provide a fast image of the target. These resultsare checked by a rigorous update of the domain electric field, allowing a more accurate calculation of the predicted data. If the accuracy is poorer than desired, rigorousinversion follows, using the resulting conductivity distribution and electric field fromLQL as a starting model. The rigorous inversion iteratively solves the field and domain equations, converting the non-linear inversion into a series of linear inversions.We test this method on synthetic and field data. The results of the inversion are veryencouraging with respect to both the speed and the accuracy of the algorithm, showingthis is a useful tool for airborne EM interpretation.